2018
DOI: 10.1002/jcp.26936
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal CPNE3 as a diagnostic and prognostic biomarker for colorectal cancer

Abstract: Exosomal proteins are emerging as relevant diagnostic and prognostic biomarkers for cancer. This study was aimed at illustrating the clinical significance of exosomal Copine III (CPNE3) purified from the plasma of colorectal cancer (CRC) patients. The CPNE3 expression levels in CRC tissues were analyzed by real-time PCR, western blot, and immunohistochemistry. Plasma exosomes were isolated to examine the CPNE3 level using ELISA. Pearson's correlation analysis was performed to investigate the CPNE3 levels betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 25 publications
0
75
0
1
Order By: Relevance
“…TRIM3 plays a role as tumor inhibition in gastric cancer, and TRIM3 knockdown can promote the growth and metastasis of gastric cancer by regulating stem cell factor and EMT regulator. By surveying the clinical studies on protein markers in exosome, most studies detected the levels of protein expression in total [11] up-regulation CD147 [12] up-regulation pancreatic ductal adenocarcinoma GPC-1 [13,14] up-regulation Gastric cancer HER-2/neu, EMMPRIN, MAGE-1, C-MET [15] up-regulation TRIM3 [16] down-regulation Prostate cancer PSA [17] up-regulation ephrinA2 [18] up-regulation survivin [19] up-regulation melanoma (phospho)Met [20] up-regulation caveolin-1 [21] up-regulation…”
Section: Protein Expression Levelmentioning
confidence: 99%
“…TRIM3 plays a role as tumor inhibition in gastric cancer, and TRIM3 knockdown can promote the growth and metastasis of gastric cancer by regulating stem cell factor and EMT regulator. By surveying the clinical studies on protein markers in exosome, most studies detected the levels of protein expression in total [11] up-regulation CD147 [12] up-regulation pancreatic ductal adenocarcinoma GPC-1 [13,14] up-regulation Gastric cancer HER-2/neu, EMMPRIN, MAGE-1, C-MET [15] up-regulation TRIM3 [16] down-regulation Prostate cancer PSA [17] up-regulation ephrinA2 [18] up-regulation survivin [19] up-regulation melanoma (phospho)Met [20] up-regulation caveolin-1 [21] up-regulation…”
Section: Protein Expression Levelmentioning
confidence: 99%
“…cancer associated proteins inside cancer-derived EVs has led to the identification of several potential disease biomarkers such as CPNE3 in colorectal cancer EVs 25 , miR-451a in non-small cell lung cancer EVs 26 , and miR-451a in pancreatic ductal adenocarcinoma EVs 27 , all of which are associated with poor disease-free survival.…”
mentioning
confidence: 99%
“…Three conclusions come from the study published by Xiao et al [ 67 ]: (1) CK19, TAG72 and CA125 were shown to be specific antigens for CRC exosomes; (2) high levels of exosomal TAG72 could specify the group of patients resistant to 5-fluorouracil (5-FU); and (3) CA125-rich small EVs could serve as a metastatic biomarker [ 67 ]. Sun et al [ 68 ] presented a comparatively small number of CRC patients with increased levels of blood exosomal copine 3 (CPNE3). In this study [ 68 ], the group of patients who were diagnosed with advanced cancer stages and distant metastasis had elevated levels of exosomal CPNE3.…”
Section: Evs In Gastrointestinal (Gi) and Liver Cancer Managementmentioning
confidence: 99%
“…Sun et al [ 68 ] presented a comparatively small number of CRC patients with increased levels of blood exosomal copine 3 (CPNE3). In this study [ 68 ], the group of patients who were diagnosed with advanced cancer stages and distant metastasis had elevated levels of exosomal CPNE3. Moreover, the combined exosomal CPNE3/carcinoembryonic antigen (CEA) test appears to be a suitable tool distinguishing CRC cases from healthy controls [ 68 ].…”
Section: Evs In Gastrointestinal (Gi) and Liver Cancer Managementmentioning
confidence: 99%
See 1 more Smart Citation